Pengaruh pengumumuman penerapan fase New Normal terhadap reaksi pasar (studi pada perusahaan yang tercatat dalam indeks LQ-45 di Bursa Efek Indonesia 20 Mei 2020) - Octarina Suma Putri; Tona Aurora Lubis; Agus Solikhin (Jurnal Dinamika Manajemen, 2021)
This study examines the effect of implementing the New Normal to improve the Indonesian economy during the Covid-19 Pandemic. In this study, the author uses purposive sampling which is incorporated in the LQ- 45 in the 2020 period. This study aims to determine the effect of abnormal returns and trading volume activity on the announcement of the implementation of the New Normal phase on LQ-45. The observation period is 11 days and the research period is H-5 before the announcement of the implementation of the New Normal phase, H-0 when the announcement of the implementation of the New Normal phase and H+5 after the announcement of the implementation of the New Normal phase. The method used in this research is the event study method. While the test equipment used is the one sample t-test and paired sample t-test. The results of this study indicate that there are abnormal returns during the event window. But there is no difference in abnormal return and trading volume activity.